The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.33158/asb.2019v5i2p47
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil volume, plant density and sowing depth on soybean seedlings characters

Abstract: Plant breeding, associated with other areas, as well as the registration and protection of cultivars, have brought relevant contributions to turn soybean into one of the most important crops for the Brazilian agribusiness. Potential additional soybean descriptors for cultivar protection purposes such as the length of the hypocotyl and epicotyl have been reported in the literature. Thus, the objective of this work was to study the effect of soil volume, plant density per pot and crop and cultivar depth on the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…The magnitudes of the coefficients of variation obtained in Experiment 1 and 2 were 7.96% and 7.35%, respectively, and they corroborate with those obtained by Nogueira et al (2008), Matsuo, Sediyama, Cruz, Oliveira andCadore (2012a) and lower than those obtained by Silva et al (2016), Chaves et al (2017), Camargos et al (2019 and Hanyu et al (2020).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The magnitudes of the coefficients of variation obtained in Experiment 1 and 2 were 7.96% and 7.35%, respectively, and they corroborate with those obtained by Nogueira et al (2008), Matsuo, Sediyama, Cruz, Oliveira andCadore (2012a) and lower than those obtained by Silva et al (2016), Chaves et al (2017), Camargos et al (2019 and Hanyu et al (2020).…”
Section: Resultssupporting
confidence: 90%
“…Concerning the fact of having identified significant difference between cultivars regarding the epicotyl length of soybean seedlings evaluated at the V2 development stage, the present work corroborates with those of Matsuo et al (2012a), Matsuo, Sediyama, Cruz andOliveira (2012b), Silva et al (2016), Chaves et al (2017), Alves et al (2019), Camargos et al (2019 and Hanyu et al (2020). The observed significance indicates that the soybean genotypes show differences among themselves, which enables successful selection of promising materials (Matsuo et al, 2012b).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Reports have shown that yield estimates for the 2017/2018 season is of 3,258 Kg/ha, which agrees with the technological packages used, becoming the second greatest average productivity in the country. Part of this success is the result of genetic improvement programs developed by Brazilian research institutes and universities (Bortolotto et al, 2015;Camargos, Campos, Alves, Ferreira, & Matsuo, 2019;Harada, Gonçalves, Kiihl, & Destro, 2015;Oda et al, 2015;Silva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Epicotyl length (EL), an important complicated and agronomically trait, was significantly related to plant density and sowing depth of soybean ( Camargos et al., 2019 ). EL exhibited the higher genetic variability at the early developmental stages of soybean, especially at V 2 and V 3 development stages ( Matsuo et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%